1 STEP: We rewrite this equation using the notation
"\\frac{\\partial}{\\partial x}\\equiv D\\quad\\text{and}\\quad\\frac{\\partial}{\\partial y}=D'\\longrightarrow\\\\[0.3cm]\n6u_{xx}-5u_{xy}-6u_{yy}=52\\cdot e^{3x+2y}\\longrightarrow\\\\[0.3cm]\n\\boxed{\\left(6D^2-5DD'-6D'^2\\right)u=52\\cdot e^{3x+2y}}"
2 STEP: Factor the resulting square expression
Note: I will use the letters "x" and "y" so that there is no confusion between the operators "D" , "D'" and the designation of the discriminant "D" :
"6D^2-5DD'-6D'^2\\longrightarrow 6x^2-5yx-6y^2=0\\\\[0.3cm]\n\\left.\\begin{array}{l}\na=6\\\\\nb=-5y\\\\\nc=-6y^2\n\\end{array}\\right| D=b^2-4ac=(-5y)^2-4\\cdot 6\\cdot(-6y)\\\\[0.3cm]\nD=25y^2+144y^2=169y^2\\longrightarrow\\sqrt{D}=13y\\\\[0.3cm]\n\\left[\\begin{array}{l}\nx_1=\\displaystyle\\frac{-b-\\sqrt{D}}{2a}=\\displaystyle\\frac{5y-13y}{12}=-\\displaystyle\\frac{2y}{3}\\\\[0.3cm]\nx_2=\\displaystyle\\frac{-b+\\sqrt{D}}{2a}=\\displaystyle\\frac{5y+13y}{12}=\\displaystyle\\frac{3y}{2}\n\\end{array}\\right.\\\\[0.3cm]\n6x^2-5xy-6y=6\\cdot\\left(x-\\left(-\\frac{2y}{3}\\right)\\right)\\cdot\\left(x-\\frac{3y}{2}\\right)\\\\[0.3cm]\n\\boxed{6D^2-5DD'-6D'^2=6\\cdot\\left(D+\\frac{2}{3}\\cdot D'\\right)\\cdot\\left(D-\\frac{3}{2}\\cdot D'\\right)}"
3 STEP: A bit of theory (without proof)
Suppose we need to solve a partial differential equation
"f\\left(D,D'\\right)u=\\varphi(x,y)"The solution consists of two parts:
"u(x,y)=C.F.+P.I.,\\,\\,\\text{where}\\\\[0.31cm]\n\\left[\\begin{array}{l}\nC.F.-\\text{the complementary function}\\\\[0.3cm]\nP.I.-\\text{Particular Integral }\n\\end{array}\\right."
To find the complementary function (C.F.)
Put "D=m" and "D'=1" in "f\\left(D, D'\\right)=0" , then we get an equation, which is called the auxillary equation.
∴ the auxillary equation is "f(m,1)=0" i.e.,
"a_0m^n + a_1m^{n\u22121} + \u00b7 \u00b7 \u00b7 + a_n = 0"
Let the roots of this equation be "m_1" , "m_2" , . . . , "m_n" . If the roots are real (or imaginary) and distinct, then
"C.F.=f_1(y+m_1x)+f_2(y+m_2x)+ \u00b7 \u00b7 \u00b7 +f_n(y+m_nx)"
To find Particular Integral (P.I.)
If
"\\varphi(x, y)=e^{ax+by}"
then
"P.I.=\\frac{1}{f\\left(D,D'\\right)}\\cdot e^{ax+by}=\\frac{1}{f(a,b)}\\cdot e^{ax+by},\\text{provided} f(a, b)\\neq0."
If "f(a,b)=0" , then
"P.I.=x\\cdot\\frac{1}{f'\\left(D, D'\\right)}\\cdot e^{ax+by},\\\\[0.3cm]\n\\text{where}\\,\\,\\,f'\\left(D, D'\\right)\\,\\,\\text{is the partial derivative of} \\,\\,f\\left(D, D'\\right) w.r.t \\,\\,D."
4 STEP: Put theory into practice
"\u0421.F. :\\left(D+\\frac{2}{3}\\cdot D'\\right)\\cdot\\left(D-\\frac{3}{2}\\cdot D'\\right)u=0\\longrightarrow\\\\[0.3cm]\n\\boxed{C.F.=f_1\\left(y-\\frac{2x}{3}\\right)+f_2\\left(y+\\frac{3x}{2}\\right)}\\\\[0.3cm]\nP.I. : P.I.=\\frac{1}{\\left(D+\\frac{2}{3}\\cdot D'\\right)\\cdot\\left(D-\\frac{3}{2}\\cdot D'\\right)}\\cdot\\frac{52}{6}\\cdot e^{3x+2y}\\\\[0.3cm]\nP.I.=\\frac{1}{\\left(3+\\frac{2}{3}\\cdot 2\\right)\\cdot\\left(3-\\frac{3}{2}\\cdot 2\\right)}\\cdot\\frac{52}{6}\\cdot e^{3x+2y}\\\\[0.3cm]\nP.I.=\\frac{1}{\\left(3+\\frac{4}{3}\\right)\\cdot\\underbrace{\\left(3-3\\right)}}_{=0}\\cdot\\frac{52}{6}\\cdot e^{3x+2y}\\\\[0.3cm]"
This means that you must first differentiate the expression "\\left(6D^2-5DD'-6D'^2\\right)" by "D" , so
"\\frac{\\partial}{\\partial D}\\left(6D^2-5DD'-6D'^2\\right)=12D-5D'"
Then,
"P.I. : P.I.=\\frac{1}{12D-5D'}\\cdot 52\\cdot e^{3x+2y}\\\\[0.3cm]\nP.I.=\\frac{1}{12\\cdot3-5\\cdot 2}\\cdot 52\\cdot e^{3x+2y}\\\\[0.3cm]\nP.I.=\\frac{52\\cdot e^{3x+2y}}{26}\\equiv 2\\cdot e^{3x+2y}\\\\[0.3cm]" Conclusion,
"u(x,y)=C.F.+P.I.\\longrightarrow\\\\[0.3cm]\n\\boxed{u(x,y)=f_1\\left(y-\\frac{2x}{3}\\right)+f_2\\left(y+\\frac{3x}{2}\\right)+2\\cdot e^{3x+2y}}"
ANSWER
"u(x,y)=f_1\\left(y-\\frac{2x}{3}\\right)+f_2\\left(y+\\frac{3x}{2}\\right)+2\\cdot e^{3x+2y}"
Comments
Dear Mohammad Khursheed Ali, please use the panel for submitting a new question.
Find the general solution of uxy-ux=ex
Leave a comment